Host-Defense Peptides as New Generation Phytosanitaries: Low Toxicity and Low Induction of Antimicrobial Resistance - Fernando Lobo; Alicia Boto (Agronomy, 2022)
Host-defense peptides (HDP) are emerging as promising phytosanitaries due to their potency, low plant, animal and environmental toxicity, and above all, low induction of antimicrobial resistance. These natural compounds, which have been used by animals and plants over millions of years to defend themselves against pathogens, are being discovered by genome mining, and then produced using biofactories. Moreover, truncated or otherwise modified peptides, including ultra-short ones, have been developed to improve their bioactivities and biodistribution, and also to reduce production costs. The synergistic combination of HDP and other antimicrobials, and the development of hybrid molecules have also given promising results. Finally, although their low induction of antimicrobial resistance is a big advantage, cautionary measures for the sustainable use of HDPs, such as the use of precision agriculture tools, were discussed.